The Phenomenon of Beauty as A Social Construction in El prestigio de la belleza by Piedad Bonnett - González Rallón, Jéssica Ivón Renata (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents an analysis of the discursive representation of beauty, from the Bajtinian terminology, which includes the ideologeme, the authoritarian word, the intrinsically convincing word, polyphony and dialogism, around the literary theory. In addition, this text exposes some findings relating to the power relations, ideologies and axiological burdens that are woven around the phenomenon of beauty as an aesthetic conception and social construction in two characters of the auto-biographic Colombian novel, The Prestige of Beauty, of piety Bonnett, published in 2010, and in which a representation of beauty is perceived with in two ways: the first one is based on the body and the second one is perceived on the intellect.